PENDEKATAN ACTIVE DATABASE SYSTEM DAN BUSINESS RULE DALAM PENGEMBANGAN SISTEM INFORMASI - M. Miftakul Amin (Jurnal Informatika, 2013)
An information system is inseparable with the database as data repository and give the data service to information system. Information system basically translate the business rule from an organization into form of algorithm programming which later then planted in application. Database which used conventionally have the character of passive and there is no controlling mechanism, that happened only mechanism just enter and its exit of data. With the existence of active of database system, a database earn the reactive behavior and conduct the controlling of information system  at database level. Business rules which is as a rule planted in application can be planted directly into database and can be used concurrently by entire/all application that using database. This writing give the study about an alternative approach of  business rules and active database system in developing an information system by planting business rules in the form of programming algorithm into database management system so that more improving the performance of information system. This active database system approach  can be implemented not only in the field of information systems development, but can be used as a data base responsive to collaborate with the control system hardware. Key words : information system, active database system, business rule